Pelaksanaan Pendaftaran Tanah Sistematis Lengkap Di Kantor Pertanahan Kota Jambi - Nazifah Nazifah; Herma Yanti; M Iqbal (Wajah Hukum, 2022)
Land registration is an important and basic activity in land management. For this reason, a number of provisions and policies related to land registration have been issued, but in reality there are still many land registration problems. The Basic Agrarian Law (UUPA) mandates that all land be registered to ensure legal certainty over land. In order to support economic growth, create legal certainty over land and avoid land conflicts, the Ministry of ATR/BPN carries out a Mapping, Registration and Certification program. Based on the above facts, a policy reconstruction of accelerated-based land registration implementation has been carried out with the target of all registered areas through the implementation of Complete Systematic Land Registration (hereinafter referred to as PTSL). Through the PTSL program, it is hoped that all community land parcels are measurable and have legality in the form of land certificates. In order for the acceleration target to be achieved, a strategy and measurable settlement steps are needed given the time constraints and with the hope that the guarantee of legal certainty will still be achieved. The experience of land certificates that prioritizes acceleration and neglects accuracy has the potential to cause data at the land office to be invalid. The purpose of this study was to determine the implementation of Complete Systematic Land Registration at the Jambi City Land Office, the obstacles and efforts to solve it in the Complete Systematic Land Registration at the Jambi City Land Office. The research method used is an empirical juridical research type, with a socio legal research approach. Sources of data used in this study are field data with interviews with related parties and library data from laws and regulations, books, journals and others related to this research. Then a descriptive-analytic data analysis was performed. So it is hoped that the results of a complete systematic land registration study at the Jambi city land office can provide guarantees of legal certainty over land. Through the PTSL program, it is hoped that all community land parcels are measurable and have legality in the form of land certificates.